SAT0206 Minimally-Invasive Technique for the Biopsy of Minor Salivary Glands: Searching for Systemic Infiltrative Diseases in Patients Presenting with SICCA Symptoms. (10th June 2014) - Brito Zeron, P.; Retamozo, S.; Bové, A.; Kostov, B.; Gheitasi, H.; Ligero, M.D.C.; Sisό-Almirall, A.; Alόs, L.; Ramos-Casals, M.
Abstract : Background: Sicca syndrome is common for several systemic diseases that may infiltrate the exocrine glands. The most frequent disease is Sjögren's syndrome (SS), but also sarcoidosis, amyloidosis or IgG4-related disease may infiltrate salivary glands. Objectives: To analyze the safety and usefulness of minimally-invasive lip biopsy technique in patients presenting with immunonegative sicca syndrome suspecting a systemic disease. Methods: A prospective analysis of 96 patients with a sicca syndrome, positive ocular tests and/or parotid scintigraphy and negative anti-Ro/La in whom a minimally-invasive biopsy of minor salivary glands (with no stitches) was carried out at a single center. Chisholm Mason score -CMS- was evaluated, together with investigation of granuloma, amyloid, IgG4-cells, lipids. Results: All biopsies but one disclosed salivary gland tissue. Histopathological diagnosis consisted of sialoadenitis (n=67), normal glandular tissue (n=22), lipoid infiltration (n=4) amyloidosis (n=1), and salivary oncocytic cystadenoma (n=1). Patients with sialoadenitis were more frequently female (87% vs 68%, p=0.046) and had a higher mean age (61.49 vs 55.27 years, p=0.047) in comparison with patients with normal biopsy. CMS classification score classified lymphoplasmocytic infiltration as absent (grade 0, n=11), mild (grade 1, n=39), moderate (grade 2, n=8), and severe (grade 3, n=4, and grade 4, n=5). No correlation was found between the degree of infiltration and ocular tests, parotid scintigraphy or with ANA, RF, monoclonal gammopathy, hypocomplementemia. Twenty-seven (40%) patients with sialoadenitis were classified as atrophic sialadenitis (periductal fibrosis and/or acinar atrophy); these patients had a higher mean age in comparison with patients with a non-atrophic sialoadenitis (69.22 vs 56.28 years, p<0.001). Eleven patients (16%) showed a chronic atrophic sialoadenitis without lymphocytic infiltration; these patients had a higher mean age in comparison with patients with lymphocytic infiltration (73.0 vs 59.2 years, p=0.002). The final diagnosis in patients with sialoadenitis consisted of: non-specific sialadenitis (n=58) and pSS (n=9). Only 7 patients (8%) reported transient adverse events recovered completely during the first 24h: 3 mild paresthesias and 4 minimum local hematoma. Conclusions: More than half patients with sicca syndrome immunonegative (Ro/La) showed a non-specific chronic sialoadenitis, that might reflect a "mild" pSS that has no place in the current classification criteria of this autoimmune disease. Lack of lymphocytic infiltration and atrophic histopathological data closely correlated with an older age. Minimally-invasive biopsy of minor salivary glands is a simple, safe, and reliable tool for the diagnosis of infiltrative systemic diseases of exocrine glands. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5132